Communications Challenges In A Smaller World - John G. Richardson; Stephen Lilley; Robert B. Gregory (Journal of Applied Communications, 1990)
Technological change and overlapping social, environmental. educational and political issues have increased the need for understandable communications among the different countries of the world. Because EngliSh is wldely used. many Americans have no other language capability and are at a disadvantage in many situations. In addition, changes in the ethnic composition of the United States have intensified the need for skills in other languages. The need for second-language skills is perhaps greater among agriculturalists than it is for other areas. The Cooperative Extension System has Important roles to play in expanding these communication skills.